Efficacy and safety of rivaroxaban vs warfarin in high-risk patients with antiphospholipid syndrome: Rationale and design of the Trial on Rivaroxaban in AntiPhospholipid Syndrome (TRAPS) trial. (March 2016) - Pengo, V; Banzato, A; Bison, E; Zoppellaro, G; Padayattil Jose, S; Denas, G
Background: New oral anticoagulants may simplify long-term therapy in conditions requiring anticoagulation. Rivaroxaban is a direct factor Xa inhibitor that has been extensively studied and is now approved for the prevention and therapy of a number of thromboembolic conditions. Objective and methods: This is a multicentre, randomized, open-label, study that will evaluate if Rivaroxaban 20 mg od (or 15 mg od in patients with moderate renal insufficiency) is non-inferior to warfarin (INR target 2.5), for the prevention of thromboembolic events, major bleeding and death in high risk (triple positive) patients with antiphospholipid syndrome. Secondary endpoints will assess the incidence of any individual component of the composite end point. An external adjudication committee will evaluate all suspected outcome events. This will be a unique trial, as it will enrol the biggest homogenous cohort of high risk APS individuals. Conclusion: The methods and the study design should be appropriate to achieve study results that are both scientifically valid and relevant to clinical practice.